The relationship between indoor environmental quality and satisfaction among polytechnic students - Ainul Zuhairi, Ainul Jasmeen; Mohd Puad, Mohd Hazwan (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
To increase the productivity and outcomes of students, indoor environmental quality is important for learning institutions. However, it is essential to know if the students are satisfied with their indoor environmental quality. The purpose of the study is to investigate the relationship between classroom indoor environmental quality and student satisfaction. Three dimensions of indoor environmental quality namely lighting, acoustics, and air quality were the focus of this study. This study also identifies the extent of classroom indoor environmental quality (lighting, acoustics and air quality) among the Polytechnic students. The collection of data was through questionnaires, approximately 500 questionnaires distributed to the students of the Polytechnic through online survey and 404 were answered. IBM SPSS Statistics 24 was used to analyse the data and Pearson Product-Moment Correlation was used to measure the relationship of the variables. The findings shows that all the independent variables (lighting, acoustics and air quality) have positive correlation with student satisfaction.